Valentines for everyone! - Gifford, Chris; Ricci, Christine Savitsky, Steven (Simon Spotlight/Nick Jr. New York, 2003)
Dora and Boots take a trip over Cupcake Mountain and across Chocolate Lake to deliver a Valentine's Day surprise to Dora's grandma, and along the way, they see all of their friends exchanging valentine treats. A lift-the-flap story